1975
DOI: 10.1073/pnas.72.12.5012
|View full text |Cite
|
Sign up to set email alerts
|

Chicken neutrophils: oxidative metabolism in phagocytic cells devoid of myeloperoxidase.

Abstract: Polymorphonuclear leukocytes isolated from chicken peritoneal exudates have been found to catalyze cyanide-insensitive stimulation of respiration and the hexose monophosphate shunt upon exposure to heat-inactivated Staphylococcus aureus. However, there was no demonstrable formate oxidation concomitant with phagocytosis in either the presence or absence of exogenous catalase. Moreover, chicken polymorphonuclear leukocytes failed to oxidize scopoletin concomitant with phagocytosis in the presence of horseradish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

1988
1988
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(21 citation statements)
references
References 19 publications
0
20
0
1
Order By: Relevance
“…However, the advent of automated differential leukocyte counting machines, where the identification of neutrophils was dependent upon a peroxidase stain, revealed that about 1 in 2000 of the general population is MPO deficient without any undue predisposition to infection [215], and the neutrophils of birds do not contain MPO [235]. …”
Section: Products Of the Oxidase And Indications As To Their Antimmentioning
confidence: 99%
“…However, the advent of automated differential leukocyte counting machines, where the identification of neutrophils was dependent upon a peroxidase stain, revealed that about 1 in 2000 of the general population is MPO deficient without any undue predisposition to infection [215], and the neutrophils of birds do not contain MPO [235]. …”
Section: Products Of the Oxidase And Indications As To Their Antimmentioning
confidence: 99%
“…These phagocytic cells are recruited to the site of an infection by both bacterial components and host inflammatory mediators (Schiffmann et al, 1975;Fernandez et al, 1978;Ford Hutchinson et al, 1980;Lee and Snyder, 1985;Ming et al, 1987;Baggiolini et al, 1989). At the site of the infection, heterophils respond to the infectious agent by phagocytizing and killing the pathogen in many cases (Penniall and Spitznagel, 1975;Powell, 1987a,b).…”
Section: Introductionmentioning
confidence: 96%
“…Most of the data describing and defining the role of avian heterophils in natural resistance to microbes have been obtained from in vitro studies (Brune et al, 1972;Topp and Carlson, 1972;Penniall and Spitznagel, 1975;Hamilton, 1979,1980;Thies et al, 1983;Andreasen et al, 1990;Latimer et al, 1990;Cordon et al, 1991). However, in order to study the contribution of heterophils as effectors in natural host defenses, direct in vivo experimental approaches must be developed.…”
Section: Introductionmentioning
confidence: 98%
“…Myeloperoxidase reacts with 0 2 -in the phagocytic vacuole and has the ability to degrade H202 to HzO through a catalase-like mechanism, and may only halogenate at low concentrations of peroxide. It is certainly not essential for immunity to infection because large numbers of symptomless subjects have been identified whose cells are completely devoid of this enzyme [79], and it is not found in neutrophils of chickens [80].…”
Section: Myeloperoxidase-mediated Halogenationmentioning
confidence: 99%